“IMPACTS AND COMPLICATIONS OF ANISOMETROPIA ON HUMAN’S EYE AND VISION” (World Bulletin of Public Health, 2023)
Anisometropia is a condition in which one eye has a significantly different refractive error from the other, which can lead to a variety of complications and impacts on human vision. Binocular vision problems, keratocounus, differences in axial length, strabismus, reduced visual acuity, amblyopia, and reduced depth perception may occur. Each eye must have optical treatment with glasses or contact lenses, and in some cases, surgery or vision therapy may be necessary. In this study 400 cases were selected to study the Anisometropia impacts and complications on the eye using different tools and optical equipment’s such as: snellen chart, Auto-Refractometry, and Retinoscopy. The selected cases were classified according to age and gender, as well as the type of pathological suffering; different statistical studies were achieved, and the results show that there is a correlation between anisometropia and the difference in dioptric power, as well as a relationship between anisometropia and different types of eye diseases such as cataract, squint, and keratoconus.a